Light response type antioxidant preparation as well as preparation method and application thereof
By developing light-responsive antioxidant preparations, using the form of Pickering emulsion or microcapsules, combined with the light responsiveness of ultraviolet or near-infrared light, the safety and insufficient application of light-responsive materials in the cosmetics field are solved, and efficient antioxidant function and controlled release of aromatic compounds are achieved.
Patent Information
- Application Number
- CN202510099565.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The application of existing photoresponsive materials in the cosmetics field is limited by the safety problems of infrared light excitation methods, and the application of ultraviolet light-triggered photoresponsive materials in the daily chemical industry is relatively lacking.
Develop a photoresponsive antioxidant preparation, using the form of Pickering emulsion or microcapsules, through cross-linking reaction and functional modification technology, cinnamate derivatives and biopolymers are used to form nanoparticles or microcapsules, combining the light responsiveness of ultraviolet or near-infrared light to achieve antioxidant function and controlled release of aromatic compounds.
It realizes the safe and efficient use of photoresponsive materials in cosmetics, and excites nanoparticles or microcapsules through light, significantly reduces the particle size, promotes the release of aromatic compounds, and enhances the antioxidant ability.
Smart Images

Figure CN119523819A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of fine chemicals and the field of cosmetic technology; more specifically, the present invention relates to a light-responsive antioxidant preparation, a preparation method and application thereof, wherein the light-responsive antioxidant preparation comprises a light-responsive core-shell structure having antioxidant properties. Background Art
[0002] The photoresponsive core-shell structure is an ordered assembly structure at the nanoscale formed by a nanomaterial encapsulating another nanomaterial through chemical bonds or other forces. This structure integrates the properties of the two materials inside and outside, and complements each other's deficiencies, with unique functions and broad application prospects.
[0003] The characteristics of photoresponsive core-shell structures include but are not limited to: (a) Photoresponsiveness: Photoresponsive core-shell structures can undergo physical or chemical changes under light, and such changes can be used to trigger specific functions of the material, such as releasing drugs, changing surface properties, etc.; (b) Core-shell structure: The core-shell structure is usually composed of a "core" and a "shell". The core and shell can be made of different materials. Through coating technology, the surface properties of the core are changed, thereby improving the stability and dispersibility of the core; (c) Functional modification: The shell layer can adjust the overall hydrophilicity of the nanoparticles, protect the surface of the core from the influence of solvents, etc., and facilitate surface functional modification.
[0004] The application fields of photoresponsive core-shell structures include: (a) Biomedicine: In the biomedical field, photoresponsive core-shell structures are used to develop multifunctional nano-diagnostic and therapeutic platforms. For example, photoresponsive porous core-shell nanoparticles can be used for cancer treatment and bioimaging; (b) Catalysis: In the catalysis field, photoresponsive core-shell structures can be used for photocatalytic reactions to improve catalytic efficiency and selectivity; (c) Batteries and gas storage: In the battery and gas storage field, photoresponsive core-shell structures can be used to design high-performance battery materials and gas storage materials to improve energy density and storage efficiency.
[0005] The preparation method of photoresponsive core-shell structure usually includes the following steps: (1) Selection of suitable core and shell materials: Select core and shell materials with specific optical and chemical properties according to application requirements; (2) Coating technology: Coat the shell material on the surface of the core material by chemical or physical methods to form an ordered core-shell structure; (3) Functional modification: Perform functional modification on the shell layer to achieve specific application functions.
[0006] In summary, due to its unique structural and functional characteristics, the photoresponsive core-shell structure has shown broad application prospects in some fields. However, the technical means required and the technical obstacles to be overcome in the application of photoresponsive core-shell structures in different fields are very different. For example, fields such as pharmaceutical sustained release / delivery mainly use photoresponsive materials to absorb infrared light to produce thermal effects for excitation to promote the release of contents in the body; and the excitation method based on the thermal effect of infrared light usually requires the presence of metal or semi-metal components / nanoparticles, and the dose required for excitation is very high, which poses a great threat to skin health and is not conducive to application in the cosmetics field. Up to now, the application of ultraviolet light-triggered photoresponsive materials in the daily chemical industry is basically blank. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a light-responsive antioxidant preparation, a light-responsive antioxidant preparation obtained by the method and its application. The light-responsive antioxidant preparation specifically includes a light-responsive Pickering emulsion and microcapsules. On this basis, a cosmetic loaded with aromatic compounds is provided.
[0008] In a first aspect of the present invention, a method for preparing a photoresponsive antioxidant preparation is provided, comprising: (1) mixing an alcohol medium of a cinnamate derivative with a biopolymer, performing a cross-linking reaction, and separating a cross-linking reaction product; (2) mixing the cross-linking reaction product with an aromatic compound to obtain a cosmetic preparation loaded with the aromatic compound and having photoresponsive properties; wherein the antioxidant preparation comprises: a Pickering emulsion or a microcapsule.
[0009] In one or more embodiments, the antioxidant preparation is a Pickering emulsion, wherein: step (1) includes: dispersing the biopolymer (preferably in water), mixing it with an alcohol medium containing a cinnamate derivative, adjusting the pH of the mixed solution to a weak alkaline state (such as pH 8.5±1), performing a cross-linking reaction, adjusting the cross-linked product to a neutral state, freeze-drying, and obtaining nanoparticles; step (2) includes: re-dissolving the nanoparticles of (1), and homogenizing with aromatic compounds in a hydrophobic phase (oil phase) to obtain a Pickering emulsion having light-responsive properties.
[0010] In one or more embodiments, step (1) includes: A: Disperse the biopolymer in water (preferably deionized water), mix thoroughly, incubate at 4±2°C, then at 90±10°C, and quickly cool to room temperature to obtain a biopolymer dispersion; B: dissolving the cinnamate derivative in an alcohol medium (preferably, the alcohol is ethanol, and the cinnamate derivative is dissolved in ethanol to form an alcohol solution of 20-80 mM, 25-70 mM, 35-65 mM, 40-60 mM or 45-55 mM), using copper ions as a catalyst and hydrogen peroxide as an oxidant, mixing and oxidizing at 10-30° C. to obtain a hydroalcoholic solution of the quinone compound; C: The hydroalcoholic solution of the quinone compound is adjusted to neutral, mixed with the biopolymer dispersion, and the pH of the mixed solution is adjusted to 8.5±1 (preferably pH 8.5±0.5, more preferably pH 8.5±0.3 or ±0.2), mixed thoroughly, and reacted for 2 to 8 hours; the reaction product is adjusted to neutral, freeze-dried, and nanoparticles are obtained.
[0011] In one or more embodiments, step (2) includes: D: The nanoparticles are dissolved in water (preferably deionized water), and the aromatic compound of the hydrophobic phase is added and emulsified to obtain the Pickering emulsion.
[0012] In one or more embodiments, the mass concentration of the biopolymer is 1 to 10 wt %, preferably 1.5 to 8 wt %, and more preferably 2 to 5 wt %.
[0013] In one or more embodiments, in A, the mixture is stirred at a speed of 600±200 rpm (preferably 600±150, 100 or 50 rpm) for 2±1 h (preferably 2±0.5 h); stored at 4±2°C (preferably 4±1°C) for 12±6 h (preferably 12±4, 2 or 1 h); and placed in a water bath at 90±10°C (preferably 90±8, 6, 4 or 2°C) for 30±20 min (preferably 30±15, 10 or 5 min).
[0014] In one or more embodiments, in B, during oxidation, 3±2 wt% (preferably 3±1.5, 1 or 0.5 wt%) of hydrogen peroxide solution is added as an oxidant, and the oxidation is carried out by stirring at 10-30°C (such as 15, 20, 25°C) and a speed of 300±200 rpm (preferably 300±150, 100 or 50 rpm).
[0015] In one or more embodiments, in B, the concentration of copper ions in the solution is 0.05-2 mol %, more preferably 0.1-1.5 mol %, for example 0.2, 0.3, 0.5, 0.7, 0.8, 1, 1.2, 1.5 or 1.8 mol %.
[0016] In one or more embodiments, in B, the volume ratio of the alcohol medium of the cinnamate derivative to the biopolymer dispersion is 1:5-20.
[0017] In one or more embodiments, in B, the molar ratio of the cinnamate derivative to hydrogen peroxide is 1:0.8-3 (preferably 1:1-5; more preferably 1:1-1.5).
[0018] In one or more embodiments, the concentration of the hydroalcoholic solution of the quinone compound is 10-120 mM; preferably 15-100 mM, such as 20, 30, 50, 80 mM.
[0019] In one or more embodiments, in C, the hydroalcoholic solution of the quinone compound is slowly adjusted to neutrality with 0.5±0.5 M (preferably 0.5±0.4, 0.3, 0.2 or 0.1 M) of sodium hydroxide, added to the biopolymer dispersion, and the pH of the mixed solution is adjusted to 8.5-9.0 with 1 M±0.6 M (preferably 1±0.5, 0.3, 0.2 or 0.1 M) of sodium hydroxide, and the reaction is stirred at 30-45° C. (such as 32, 35, 38, 40, 42° C.) at a speed of 600±200 rpm (preferably 600±150, 100 or 50 rpm) for 2-8 h (such as 3, 4, 5, 6 h).
[0020] In one or more embodiments, in C, after the reaction product is adjusted to neutrality, the process further comprises: removing insoluble matter, harvesting the clear liquid and performing freeze-drying.
[0021] In one or more embodiments, in D, the nanoparticles are dissolved in water (preferably deionized water), a hydrophobic phase (aromatic compound) is added, and emulsified with a high-speed disperser at a rotation speed of 8000±2000rpm (preferably 8000±1500, 1000 or 500rpm) for 5±4min (preferably 0.5±3, 2 or 1min), and allowed to stand overnight at 4±2°C (preferably 4±1°C) to obtain a Pickering emulsion.
[0022] In one or more embodiments, in step (2), the mass concentration of the nanoparticles is 0.5 to 20 mg / mL (such as 1, 2, 4, 6, 8, 10, 12 or 15 mg / mL).
[0023] In one or more embodiments, the volume fraction of the hydrophobic phase is 3 to 80 v / v% (eg, 5, 10, 15, 20, 30, 40, 50, 60, 70, 74 or 75 v / v%).
[0024] In one or more embodiments, the antioxidant preparation is a microcapsule, wherein: step (1) comprises: mixing and dispersing an alcohol medium containing a cinnamate derivative with a biopolymer, and adding water to form a co-solvent; adjusting the pH of the mixed solution to a weak alkaline state (such as pH 8.0±0.6), performing a cross-linking reaction, adjusting the cross-linked product to a neutral state, and freeze-drying to obtain a graft; step (2) comprises: redissolving the graft of (1), mixing it with an aromatic compound in a hydrophobic phase, and separating a portion having a molecular weight greater than 3500 Da to obtain a microcapsule having a light-responsive property.
[0025] In one or more embodiments, step (1) includes: A': dissolving the cinnamate derivative in an alcohol medium (preferably forming an alcohol solution with a cinnamate derivative concentration of 5 to 80 mM, more preferably 8 to 60 mM or 10 to 50 mM), using copper ions as a catalyst and hydrogen peroxide as an oxidant, mixing and oxidizing at 10 to 30°C to obtain a hydroalcoholic solution of the quinone compound; B': dispersing the biopolymer in a hydroalcoholic solution of the quinone compound, and then adding an equal volume of water (preferably deionized water) to form a cosolvent (alcohol-water cosolvent); C': adjust the pH of the mixed solution to 8.0±0.6 (preferably pH 8.0±0.5, more preferably pH 8.0±0.3 or ±0.2), fully mix at 30-45°C, and react for 2-8 hours; adjust the reaction product to neutral, freeze-dry, and obtain a grafted product.
[0026] In one or more embodiments, step (2) includes: D': The grafted product is dissolved in water (preferably deionized water), and an aromatic compound of a hydrophobic phase is added. The part with a molecular weight greater than 3500 Da is cut off by dialysis to obtain a microcapsule with light-responsive properties.
[0027] In one or more embodiments, the mass concentration of the biopolymer is 0.1-2 wt %, preferably 0.15-1 wt %, and more preferably 0.2-0.5 wt %.
[0028] In one or more embodiments, during oxidation in A', 3±2wt% (preferably 3±1.5, 1 or 0.5wt%) of hydrogen peroxide solution is added as an oxidant, and the oxidation is carried out by stirring at 10-30°C (such as 15, 20, 25°C) and a speed of 300±200 rpm (preferably 300±150, 100 or 50rpm).
[0029] In one or more embodiments, in A', the copper ions include (but are not limited to) from copper chloride, such as adding anhydrous copper chloride to form copper ions in the solution. Preferably, the concentration of copper ions in the solution is 0.05-2 mol%, more preferably 0.1-1.5 mol%, such as 0.2, 0.3, 0.5, 0.7, 0.8, 1, 1.2, 1.5 or 1.8 mol%.
[0030] In one or more embodiments, in A', the molar ratio of the cinnamate derivative to hydrogen peroxide is 1:0.8-3 (preferably 1:1-5; more preferably 1:1-1.5).
[0031] In one or more embodiments, the concentration of the hydroalcoholic solution of the quinone type compound is 5-80 mM, preferably 8-60 mM, more preferably 10-50 mM, such as 20, 30, 40 mM.
[0032] In one or more embodiments, in C', the pH of the co-solvent is adjusted to pH 8.0±0.6 using 1 M±0.6 M (preferably 1±0.5, 0.3, 0.2 or 0.1 M) sodium hydroxide, and the reaction is stirred at 30-45°C (such as 32, 35, 38, 40, 42°C) at a speed of 800±200 rpm (preferably 800±150, 100 or 50 rpm) for 2-8h (such as 3, 4, 5, 6h).
[0033] In one or more embodiments, in D', water (preferably deionized water) is used as the dialysate, and the water can be replaced during the dialysis process.
[0034] In one or more embodiments, in step (2), the mass concentration of the grafted material is 0.02-0.8 wt % (eg, 0.05, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 wt %).
[0035] In one or more embodiments, the volume fraction of the hydrophobic phase is 1 to 20 v / v% (eg, 2, 3, 5, 6, 8, 10, 12 or 15 v / v%).
[0036] In one or more embodiments, the cinnamate derivatives include compounds of the following structural formula: ; Wherein, R1 is selected from long-chain alkanes, long-chain olefins, benzene or benzene homologues; R 2~ R6 are each independently selected from a hydrogen atom, a hydroxyl group, an aldehyde group, a methoxy group or a carbonyl group;
[0037] The cinnamate derivatives include: caffeic acid phenethyl ester, caffeic acid benzyl ester, caffeic acid benzyl ester, caffeic acid n-octyl ester or caffeic acid-1,1-dimethylallyl ester, or a combination thereof.
[0038] In one or more embodiments, the biopolymer includes protein or polysaccharide; the antioxidant preparation is a Pickering emulsion, and the biopolymer includes: soy protein isolate, soy protein hydrolyzate, whey protein, whey protein isolate, lactoferrin, sericin, ovalbumin, egg yolk protein, collagen, hydrolyzed collagen, bovine serum albumin, ε-polylysine or polylysine, or a combination thereof.
[0039] In one or more embodiments, the antioxidant preparation is a microcapsule, and the biopolymer includes: carboxymethyl chitosan, N,N,N-trimethyl chitosan, hydroxypropyl chitosan, chitosan, amino dextran, amino hyaluronic acid, or a combination thereof.
[0040] In one or more embodiments, the hydrophobic phase (oil phase) includes: peppermint essential oil, limonene, tea tree oil, eucalyptus oil, soybean oil, castor oil, palm oil, jojoba oil, shea butter, almond oil, grape seed oil, tea seed oil, lavender oil or fatty acid esters, or a combination thereof.
[0041] In one or more embodiments, the alcohol medium includes ethanol, isopropanol or tert-butanol, or a combination thereof.
[0042] In one or more embodiments, the copper ions include, but are not limited to, copper ions from copper chloride or copper sulfate, such as by adding anhydrous copper chloride or anhydrous copper sulfate to form copper ions in the solution.
[0043] In one or more embodiments, the quinone type compound includes: a semiquinone compound, an o-benzoquinone compound or a free radical polymer.
[0044] In another aspect of the present invention, a photoresponsive antioxidant preparation is provided, which is prepared by any of the above methods.
[0045] In one or more embodiments, the light-responsive antioxidant preparation is a Pickering emulsion, wherein the average particle size of the nanoparticles is 20 to 50 nm, and the particle size of the nanoparticles is significantly reduced after light exposure.
[0046] In one or more embodiments, the light-responsive antioxidant preparation is a Pickering emulsion, and the droplet diameter thereof is 200 nm to 1.5 um; the droplet diameter is significantly reduced after light exposure.
[0047] In one or more embodiments, the light-responsive antioxidant preparation is a microcapsule, wherein the average particle size of the microcapsules is 500 nm to 1.5 um, and the particle size of the microcapsules is significantly reduced after light exposure.
[0048] In one or more embodiments, the light includes ultraviolet light or near infrared light.
[0049] In one or more embodiments, the light may be natural light, and the natural light may contain ultraviolet light or near infrared light.
[0050] In another aspect of the present invention, there is provided an application of the light-responsive antioxidant preparation for preparing cosmetics or skin care products, wherein the aromatic compound can be released in a controlled manner.
[0051] Other aspects of the present invention will be apparent to those skilled in the art in view of the disclosure herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 , The UV-visible absorption spectrum of the nanoparticles prepared in Example 1 is used to characterize the properties of the nanoparticles. The wavelength is the abscissa and the absorbance (au) is the ordinate, where a is the soy protein isolate and b is the nanoparticles.
[0053] Figure 2 , Dynamic light scattering (DLS) of the nanoparticles prepared in Example 1 is used to characterize the change in particle size of the prepared nanoparticles before and after UV-340 irradiation. The particle size (d.nm) is the abscissa and the volume percentage (%) is the ordinate.
[0054] Figure 3 , ABTS and FRAP graphs of the nanoparticles prepared in Example 1, used to characterize the in vitro antioxidant capacity of the nanoparticles. Taking 10 mg / mL nanoparticles as the benchmark, the dilution factor as the abscissa, and TEAC (mmol / L) as the ordinate, where (a) is the ABTS graph of the graft, (b) is the FRAP graph of the graft, and TEAC represents the concentration of the Trolox positive control.
[0055] Figure 4 , TEM image of the Pickering emulsion prepared in Example 2.
[0056] Figure 5 , SEM image of the Pickering emulsion prepared in Example 2.
[0057] Figure 6 , DLS graph of the Pickering emulsion prepared in Example 2, used to characterize the change in particle size of the prepared Pickering emulsion before and after UV-340 irradiation.
[0058] Figure 7, DLS graph of the Pickering emulsion prepared in Example 3, used to characterize the change in particle size of the prepared Pickering emulsion before and after UV-340 irradiation.
[0059] Figure 8 , DLS graph of the Pickering emulsion prepared in Example 4, used to characterize the change in particle size of the prepared Pickering emulsion before and after UV-340 irradiation.
[0060] Fig. 9 , DLS graph of the Pickering emulsion prepared in Example 4, used to characterize the change in zeta potential of the prepared Pickering emulsion before and after UV-340 illumination. Zeta potential (mv) is the abscissa and total counts are the ordinate.
[0061] Fig.10 The appearance pictures of the high internal phase emulsion of Example 5 after natural light, ultraviolet light, storage at 40°C in the dark, and storage at room temperature in the dark, intuitively show the release of the oil phase in the emulsion. The high internal phase Pickering emulsion is in the form of a semi-solid cream when stable. If unstable precipitation of the oil phase occurs, a phase transition will occur. No obvious phase transition occurred during heat treatment and storage at room temperature in the dark, while both natural light and ultraviolet light can promote the formation of phase transition. This shows that the light response behavior of the nanoparticles in the emulsion leads to the controlled release of the oil phase, that is, the phase transition process occurs.
[0062] Fig.11 , Fourier transform infrared spectra of the graft and carboxymethyl chitosan in Example 6, used to characterize the properties of the graft. Wavelength (nm) is the abscissa, where a is carboxymethyl chitosan and b is the graft.
[0063] Fig.12 , ABTS and FRAP graphs of the graft prepared in Example 6, used to characterize the in vitro antioxidant capacity of the graft. Taking 1 mg / mL graft as the benchmark, the dilution multiple as the abscissa, and TEAC (mmol / L) as the ordinate, where (a) is the ABTS graph of the graft, (b) is the FRAP graph of the graft, and TEAC represents the concentration of the Trolox positive control.
[0064] Fig.13 , laser confocal microscopy images of the microcapsules prepared in Example 7, used to characterize the loading conditions of the microcapsules (ac).
[0065] Fig.14 , the contact angle comparison diagram in Example 8 is used to characterize the amphiphilicity of the graft. The contact angle (θ) is the angle between the water and air interface, where (a) is carboxymethyl chitosan and (b) is the graft.
[0066] Fig.15The DLS graph of Example 8 is used to characterize the particle size change of the microcapsules before and after UV-340 irradiation. The particle size (d.nm) is the abscissa and the volume percentage (%) is the ordinate.
[0067] Fig.16 , Example 9: Contact angle comparison diagram, used to characterize the amphiphilicity of the grafted material. The contact angle (θ) is the angle between the water and air interface, where (a) is carboxymethyl chitosan and (b) is the grafted material.
[0068] Fig.17 , DLS graph of the microcapsules prepared in Example 9, characterizing the change in particle size of the microcapsules before and after irradiation with UV-340.
[0069] Fig.18 , Example 8, 9 release amount of microcapsules prepared with ultraviolet UV-340 illumination time change graph. The placement time (h) is the horizontal axis, the release rate of the core material (%) is the vertical axis, the ultraviolet UV-340 illumination groups are a and b, where a is the microcapsule prepared in Example 8, b is the microcapsule prepared in Example 9, and the control is the microcapsule prepared in Example 3 under dark conditions. DETAILED DESCRIPTION
[0070] After in-depth research, a type of preparation (composition) that is responsive to light and has antioxidant effect is revealed, the preparation includes Pickering emulsion or microcapsule, which can form cosmetics or skin care products, or be used as an active ingredient of cosmetics or skin care products. The present invention also provides a method for preparing the preparation.
[0071] In the daily chemical industry, photoresponsive materials that use light signals to control the release of core ingredients have rarely been successfully prepared. The present invention changes this. Specifically: (1) From the perspective of the trade-off between material coating performance and light responsiveness, the coating ability of responsive materials has always been a problem in the daily chemical industry; however, the present invention utilizes the characteristics of Pickering emulsions to prepare responsive materials that can load up to 80% of the oil phase. (2) The preparation of most photoresponsive materials is relatively complex and costly; however, the present invention utilizes a simple preparation method, which is a biomimetic synthesis with high economic benefits and is suitable for the cosmetics industry. (3) The daily chemical industry has high requirements for biosafety. The present invention brings beneficial antioxidant properties during the preparation process, and the introduction of protein and polysaccharide components increases biocompatibility. (4) The daily chemical industry has not yet seen a responsive method that can cause the emulsion / microcapsule particle size to decrease under light, which is a major difficulty, but the present invention successfully obtained such products.
[0072] In the present invention, ultraviolet or near-infrared light (phototherapy band) in natural light is innovatively used to excite the shell structure, so that mild cis-trans isomerization and physical changes can be carried out at lower concentrations, without relying on the triggering method of thermal effects (metal / semi-metal components), and has unique application advantages in cosmetics.
[0073] Core-shell structure The core-shell structure is an ordered assembly structure formed by coating one material on the surface of another material.
[0074] In the present invention, cinnamate derivatives are used, wherein the cinnamate groups are hydrophobically modified on biopolymers (such as proteins or polysaccharides), and the modified biopolymers are obtained and used as shell structures. After adding appropriate core components, the shell structure and the core components are assembled under optimized conditions to form a core-shell structure, including Pickering emulsions or microcapsules.
[0075] After the modified biopolymer with shell structure obtained by the present invention is irradiated with light (preferably ultraviolet light), the cinnamate groups in the shell undergo cis-trans isomerization, so that the particle size of the core-shell structure is reduced and extrusion rearranged, thereby achieving controlled release of the core component.
[0076] As used in the present invention, the "hydrophobic phase" and "oil phase" can be used interchangeably.
[0077] Antioxidant photoresponsive core-shell structures: Pickering emulsions Pickering emulsion is an emulsion system stabilized only by solid particles. In the process of using protein to prepare Pickering emulsion, the semi-solid shell is usually in the form of a hydrocolloid, such as a gel or a film. The Pickering emulsion prepared in the present invention does not require the presence of a surfactant and can provide strong stability to the emulsion with a very small addition amount.
[0078] The photoresponsive Pickering emulsion of the present invention is prepared by dispersing a biopolymer in deionized water, adjusting the pH of the solution to deprotonate it, and then adding an alcohol medium containing a cinnamate derivative to crosslink it, and obtaining nanoparticles after sufficient reaction. The obtained nanoparticles are freeze-dried, and then redissolved in deionized water as an emulsifier, and mixed with an oil phase to obtain a Pickering emulsion with photoresponsiveness.
[0079] In the structure of the cinnamate derivative, the electron-deficient benzene ring containing α,β-unsaturated aldehydes and ketones can react with the electron-rich thiol or amino group of the biopolymer by Michael addition and Schiff base reaction, thereby obtaining a covalent crosslinked product.
[0080] In the cinnamate derivative, the vinyl group has the ability of photoinduced cis-trans isomerization, and the side chain group has hydrophobicity, so as to serve as the photoresponsive group and hydrophobic part of the biopolymer. By modifying the surface or inner surface of the nanoparticle, its hydrophobicity is enhanced to make it suitable as an emulsifier, thereby obtaining a Pickering emulsion with photoresponsiveness.
[0081] As a preferred embodiment of the present invention, a method for preparing a nanoparticle-stabilized Pickering emulsion comprises: A1: The biopolymer was dispersed in deionized water according to a certain ratio, stirred at 600 r for 2 h, and then stored at 4 °C for 12 h. It was then placed in a 90 °C water bath for 30 min and quickly cooled to room temperature to obtain a biopolymer dispersion; B1: Dissolve the cinnamate derivative in an alcohol medium, add copper ions as a catalyst, then add 3 wt% hydrogen peroxide solution as an oxidant, stir and oxidize at 10-30°C at a speed of 300 r to obtain a hydroalcoholic solution of a quinone compound; C1: The hydroalcoholic solution of the quinone compound was slowly adjusted to neutral with 0.5 M sodium hydroxide, then added to the biopolymer dispersion, and the pH of the mixture was adjusted to 8.5-9.0 with 1 M sodium hydroxide. The mixture was stirred at 30-40 °C and 600 r for 2-3 h. D1: The reaction product was extracted and dissolved in deionized water to obtain an aqueous solution of nanoparticles. A certain volume of oil phase was then added and emulsified using a high-speed disperser at 8000 rpm for 5 min and allowed to stand overnight at 4°C to obtain a Pickering emulsion.
[0082] According to some preferred embodiments of the present invention, the preparation method further comprises: when the biopolymer is hydrated and stratified, firstly stirring and dispersing it, and then heating it in a water bath at 90° C. after the solution is uniform and stable.
[0083] According to some preferred embodiments of the present invention, the mass concentration of the biopolymer is 2-5 wt %.
[0084] According to some preferred embodiments of the present invention, the alcohol medium includes: ethanol, isopropanol, tert-butyl alcohol. More preferably, the alcohol medium is selected from ethanol.
[0085] According to some preferred embodiments of the present invention, the concentration of the hydroalcoholic solution of the quinone type compound is 15-100 mM.
[0086] According to some preferred embodiments of the present invention, the copper ion catalyst includes copper ions from anhydrous cupric chloride and anhydrous cupric sulfate. More preferably, the copper ion catalyst comes from anhydrous cupric chloride.
[0087] According to some preferred embodiments of the present invention, the molar concentration of the copper ion catalyst is 0.1-0.5 mol %.
[0088] According to some preferred embodiments of the present invention, the molar ratio of the cinnamate derivative to hydrogen peroxide (such as 3 wt % hydrogen peroxide solution) is 1:1 to 1.5.
[0089] According to some preferred embodiments of the present invention, the volume ratio of the alcohol medium of the cinnamate derivative to the biopolymer dispersion is 1:5-20.
[0090] According to some preferred embodiments of the present invention, the quinone type compound includes: a semiquinone compound, an o-benzoquinone compound and a free radical polymer.
[0091] According to some preferred embodiments of the present invention, the reaction pH is preferably 8.5, and the temperature is preferably 35°C.
[0092] According to some preferred embodiments of the present invention, the extraction of the reaction product comprises the following steps: adjusting the pH of the obtained mixed solution back to 7.0 with 0.5 M hydrochloric acid and separating the insoluble matter therein, and freeze-drying the obtained clear solution to obtain the nanoparticles.
[0093] According to some preferred embodiments of the present invention, the mass concentration of the nanoparticles is 1-10 mg / mL.
[0094] According to some preferred embodiments of the present invention, the volume fraction of the oil phase is 5 to 74 v / v%.
[0095] According to some preferred embodiments of the present invention, the cinnamate derivative is selected from one or more of caffeic acid phenethyl ester, caffeic acid benzyl ester, caffeic acid benzyl ester, caffeic acid n-octyl ester, and caffeic acid-1,1-dimethylallyl ester.
[0096] According to some preferred embodiments of the present invention, the biopolymer is selected from one or more of soy protein isolate, soy protein hydrolyzate, whey protein, whey protein isolate, lactoferrin, sericin, ovalbumin, yolk protein, collagen, hydrolyzed collagen, bovine serum albumin, ε-polylysine, and polylysine.
[0097] According to some preferred embodiments of the present invention, the oil phase is selected from one or more of peppermint essential oil, tea tree oil, eucalyptus oil, soybean oil, castor oil, palm oil, jojoba oil, shea butter, almond oil, grape seed oil, and tea seed oil.
[0098] According to some preferred embodiments of the present invention, the average particle size of the nanoparticles is 20-50 nm, and the average droplet diameter of the Pickering emulsion is 200 nm-1.5 um.
[0099] The preparation method of the present invention firstly performs heat denaturation treatment on the biopolymer to destroy disulfide bonds and hydrophobic interactions to increase its solubility in a water-based system, thereby obtaining nanoparticle aggregates. After the cinnamate derivatives undergo oxidation reaction, various quinone compounds containing electron-deficient structures can be obtained. The quinone compounds are uniformly dispersed into the biopolymer through an alcohol medium, and Michael addition or Schiff base reaction occurs with the amino acid side chains containing thiol or amino groups in the biopolymer.
[0100] The vinyl group in cinnamate derivatives is the key group for photoisomerization. Copper ions can not only catalyze the oxidation of cinnamate derivatives through coordination, but also enhance the electrophilicity of quinone carbonyl as Michael acceptor in subsequent reactions, inhibiting the participation of vinyl ester groups in Michael addition reactions. Trace amounts of copper ions in the system have no adverse effects.
[0101] In the subsequent reaction, the more hydrophilic nanoparticle aggregates and the more hydrophobic quinone compounds undergo covalent crosslinking to form modified nanoparticles. Due to the presence of cinnamate groups on the particle surface, the nanoparticles acquire photoresponsiveness. The Pickering emulsion is stabilized by the shell structure composed of nanoparticles. Once the ultraviolet UV-340 light excites the nanoparticles in the shell, the particle size and polydispersity change, triggering the reorganization of the emulsion interface structure, causing the emulsion droplet diameter to decrease and affecting the stability of the emulsion.
[0102] The technical solution for preparing Pickering emulsion of the present invention includes at least the following excellent technical effects: (1) The preparation methods of the present invention all use non-toxic or low-toxic solvents, have simple reaction steps, low equipment requirements, low energy consumption, simple process conditions, and simple post-treatment.
[0103] (2) The present invention can endow the modified nanoparticles with light responsiveness when preparing them. The cinnamate derivatives on the surface of the particles will undergo cis-trans isomerization after being irradiated with ultraviolet UV-340, resulting in a decrease in the particle size and PDI of the nanoparticles.
[0104] (3) The catalyst used in the present invention has a secondary catalytic effect, thereby increasing the utilization rate.
[0105] (4) The Pickering emulsion prepared by the present invention has a unique light response behavior. The dynamic changes of the nanoparticles after UV-340 irradiation will trigger the reorganization of the emulsion interface structure, resulting in a decrease in the emulsion droplet diameter and PDI. When the oil phase concentration in the emulsion is ≥74%, UV-340 irradiation will cause the phase change of the emulsion and the precipitation of the oil phase, achieving the effect of controlled release.
[0106] (5) The nanoparticles and Pickering emulsion prepared by the present invention have excellent biological safety. The nanoparticles have excellent emulsifying properties and can be used to prepare high internal phase emulsions at extremely low concentrations.
[0107] Antioxidant photoresponsive core-shell structures: microcapsules Microcapsules are tiny enclosed structures composed of a solid, liquid or gas core material and an external film-forming material. To date, there have been no reports on the method of preparing microcapsules by self-assembly using modified polysaccharides as both the shell structure and the photoresponsive material.
[0108] The photoresponsive microcapsules of the present invention are prepared by dissolving a biopolymer in deionized water, adjusting the pH of the solution to deprotonate it, and then adding an alcohol medium containing a cinnamate derivative to crosslink it, and obtaining a graft with photoresponsiveness in a cosolvent after sufficient reaction. The obtained graft is freeze-dried, redissolved in a cosolvent, mixed with an oil phase, and then the cosolvent is removed to obtain a microcapsule with photoresponsiveness.
[0109] In the structure of the cinnamate derivative, the electron-deficient benzene ring containing α, β-unsaturated aldehydes and ketones can undergo Michael addition reaction with the electron-rich amino group of the biopolymer to obtain a covalent cross-linked product.
[0110] In the cinnamate derivative, the vinyl group has the ability of photoinduced cis-trans isomerization, and the side chain group has hydrophobicity, thereby serving as the photoresponsive group and hydrophobic part of the biopolymer. The biopolymer serves as the hydrophilic part, thereby forming a graft structure and self-assembling into a microcapsule with photoresponsiveness.
[0111] As a preferred embodiment of the present invention, a method for preparing microcapsules comprises: A2: Dissolve the cinnamate derivative in an alcohol medium, add copper ions as a catalyst, then quickly add 3wt% hydrogen peroxide solution as an oxidant, stir and oxidize at 10-30°C at a speed of 300 r to obtain a hydroalcoholic solution of a quinone compound.
[0112] B2: The biopolymer is dispersed in a hydroalcoholic solution of the quinone compound in a certain proportion, and then an equal volume of deionized water is added to form a co-solvent.
[0113] C2: Use 1 M sodium hydroxide to adjust the pH of the co-solvent to 7.5-8.0, and stir the reaction at 800 r at 35-45 °C for 6 h.
[0114] D2: extract the reaction product, redissolve the grafted product in an alcohol-water co-solvent, add a certain volume of the hydrophobic phase, and then dialyze to remove the alcohol solvent to obtain microcapsules loaded with the hydrophobic phase.
[0115] According to some preferred embodiments of the present invention, the preparation method further comprises: when the biopolymer cannot be completely dissolved in the co-solvent, adding a certain volume of deionized water until the biopolymer is completely dissolved.
[0116] According to some preferred embodiments of the present invention, the mass concentration of the biopolymer is 0.2-0.5 wt%.
[0117] According to some preferred embodiments of the present invention, the alcohol medium includes: tert-butyl alcohol, ethanol, isopropyl alcohol. More preferably, the alcohol medium is selected from tert-butyl alcohol.
[0118] According to some preferred embodiments of the present invention, the concentration of the hydroalcoholic solution of the quinone type compound is 10-50 mM.
[0119] According to some preferred embodiments of the present invention, the copper ion catalyst includes anhydrous copper chloride and anhydrous copper sulfate. More preferably, the copper ion catalyst is selected from anhydrous copper chloride.
[0120] According to some preferred embodiments of the present invention, the molar concentration of the copper ion catalyst is 0.1 to 1 mol %.
[0121] According to some preferred embodiments of the present invention, the molar ratio of the cinnamate derivative to hydrogen peroxide (such as 3 wt % hydrogen peroxide solution) is 1:1 to 1.5.
[0122] According to some preferred embodiments of the present invention, the quinone type compound includes: a semiquinone compound, an o-benzoquinone compound and a free radical polymer.
[0123] According to some preferred embodiments of the present invention, the reaction pH is preferably 7.5, and the temperature is preferably 40°C.
[0124] According to some preferred embodiments of the present invention, the extracting the reaction product comprises: adjusting the pH of the product to 7.0 using 0.1 M acetic acid, separating the insoluble matter of the reaction product, and freeze-drying the obtained clear liquid to obtain the grafted product.
[0125] According to some preferred embodiments of the present invention, the mass concentration of the grafted substance is 0.05-0.2 wt %.
[0126] According to some preferred embodiments of the present invention, the volume fraction of the hydrophobic phase is 1-10%.
[0127] According to some preferred embodiments of the present invention, the cinnamate derivative is selected from one or more of caffeic acid phenethyl ester, caffeic acid benzyl ester, caffeic acid benzyl ester, caffeic acid n-octyl ester, and caffeic acid-1,1-dimethylallyl ester.
[0128] According to some preferred embodiments of the present invention, the biopolymer is selected from one or more of carboxymethyl chitosan, N,N,N-trimethyl chitosan, hydroxypropyl chitosan, chitosan, amino dextran, and amino hyaluronic acid.
[0129] According to some preferred embodiments of the present invention, the hydrophobic phase is selected from one or more of limonene, lavender oil, peppermint essential oil, tea tree oil, eucalyptus oil, and fatty acid esters.
[0130] According to some preferred embodiments of the present invention, the alcohol solvent is tert-butanol.
[0131] According to some preferred embodiments of the present invention, the dialysate during dialysis is deionized water, the molecular weight cutoff of the dialysis bag is 3500 Da, the dialysis time is 6 to 12 h, and the water is changed every 3 h.
[0132] According to some preferred embodiments of the present invention, the air-water interface contact angle of the graft is ≥60°, and the average particle size of the microcapsules is 500 nm to 1.5 um.
[0133] In the above preparation method of the present invention, after the cinnamate derivative is subjected to oxidation reaction, a variety of quinone compounds containing electron-deficient structures can be obtained. The Michael addition reaction occurs with the side chain containing amino groups in the biopolymer by forming a co-solvent. In addition, tert-butyl alcohol as a large steric hindrance solvent can effectively inhibit the transesterification during the reaction and is also conducive to the freeze-drying of the product.
[0134] In the subsequent treatment, the covalent cross-linked product will form a porous aerogel after freeze drying, maintaining the stability of the structure. Since the cinnamate group is photoresponsive and the microcapsules are formed by self-assembly of the grafts, once the grafts undergo cis-trans isomerization after UV-340 irradiation, this will directly or indirectly affect the spatial arrangement of the microcapsule shell, thereby extruding and releasing the core components by reducing the particle size.
[0135] The technical solution for preparing microcapsules of the present invention has at least the following excellent technical effects: (1) The preparation methods of the present invention all use non-toxic or low-toxic solvents, have simple reaction steps, low equipment requirements, low energy consumption, simple process conditions, and simple post-treatment.
[0136] (2) The present invention can impart light responsiveness to the grafted material while preparing it. The cinnamate derivatives undergo cis-trans isomerization after being irradiated with ultraviolet UV-340, resulting in a decrease in the particle size and PDI of the microcapsules.
[0137] (3) The present invention can be carried out under neutral conditions and the reaction is mild.
[0138] (4) The microcapsules prepared by the present invention have novel characteristics and are significantly different from the release behavior of existing microcapsules. When the particle size of the microcapsules is reduced, the core components will be squeezed and released, achieving the effect of controlled release.
[0139] The present invention is described in detail below in conjunction with the embodiments and drawings, but it should be understood that the embodiments and drawings are only used to exemplify the present invention and do not constitute any limitation on the protection scope of the present invention. All reasonable changes and combinations within the scope of the inventive concept of the present invention fall within the protection scope of the present invention.
[0140] Materials and methods The instrument used for UV-visible absorption spectrum measurement is Shimadzu UV-3600i Plus from Japan. The measurement steps or test conditions are as follows: turn on the machine and preheat for 20 min, dilute the nanoparticle dispersion to 0.2 mg / mL with deionized water and put it into a quartz cuvette, set the scanning wavelength to 200-1000 nm. Use a barium sulfate standard white plate for baseline scanning, place the sample on the sample side after calibration, and collect the sample's absorbance spectrum at 25°C.
[0141] The instrument used for dynamic light scattering (DLS) measurement is the British Malvern Zetasizer Nano ZS90; the measurement steps or test conditions are as follows: 1 mL of the upper emulsion is aspirated and diluted 5 to 10 times with water; the dilution multiple of each sample is the same, and then it is added dropwise to the DLS sample cell, and the average droplet diameter and zeta potential of the emulsion are tested by DLS at 25°C. Each sample is tested three times in parallel, and the results are expressed as the arithmetic mean.
[0142] Transmission electron microscope (TEM) test instrument: American FEI Talos F200X G2; measurement steps or test conditions are: drop the emulsion on the copper mesh, let it dry for 30 minutes under the fume hood, and take TEM images at a voltage of 100 kV.
[0143] Scanning electron microscope (SEM) test instrument: German ZEISS Sigma 300; measurement steps or test conditions: freeze-dried nanoparticles are directly adhered to the conductive glue, and gold is sprayed for 45 s using a Quorum SC7620 sputtering coater at 10 mA; then the sample morphology is photographed using an SEM with an accelerating voltage of 3 kV and a SE2 secondary electron detector.
[0144] ABTS and FRAP total antioxidant capacity test: Use the total antioxidant capacity test kit (ABTS method and FRAP method) to evaluate the total antioxidant capacity of the nanoparticles. For specific steps, refer to the kit instructions. Prepare Trolox solution and The total antioxidant capacity and antioxidant capacity of the nanoparticles were evaluated by ABTS and FRAP methods. The reducing power was determined.
[0145] Determination of DPPH free radical scavenging rate: Antioxidant test was performed using the DPPH free radical scavenging ability kit. For specific steps, please refer to the kit instructions. The assay tube A1 (containing the nanoparticles to be tested and DPPH solution), the control tube A2 (containing only DPPH solution, no sample) and the blank tube A3 (containing the nanoparticles to be tested and the solvent) were set up respectively. All test tubes were kept at room temperature away from light for 30 minutes to ensure that the reaction was fully carried out. After the reaction was completed, the precipitate was removed by centrifugation, and the supernatant was collected. The absorbance value A of the solution in each tube at a wavelength of 517nm was determined by a spectrophotometer, which corresponded to the assay tube A1, the control tube A2 and the blank tube A3 respectively. The scavenging rate of DPPH free radicals was calculated according to the following formula: DPPH clearance rate (%) = [(A2 + A3) - A1] / A2 × 100%.
[0146] Emulsion appearance photography: It was carried out in a DOHO D60 standard light box, with black as the background color, adjusted to 6500 k color temperature, and focused and photographed with the rear camera of a mobile phone after manual white balance.
[0147] Fourier transform infrared spectroscopy instrument: American Thermo Fisher Scientific Nicolet iS20; measurement steps or test conditions: sample and potassium bromide are mixed, ground, and then pressed into tablets. Fourier transform infrared spectroscopy at 4000-500 cm -1 Recording within the range with a resolution of 4 cm -1 .
[0148] Laser confocal microscope instrument: Leica STELLARIS 5; measurement steps or test conditions are as follows: add 10 uL 1 mg / mL calcofluor white dye solution and 10 uL 1 mg / mL Nile red dye solution to 1 mL sample solution, stain for 10 minutes, take 10 uL sample and place it on a slide, set the excitation wavelength to 405 nm and 559 nm, receive emission at 432 nm and 635 nm, and observe under a laser confocal microscope.
[0149] Contact angle test: The measurement steps or test conditions are as follows: Place the sample on a Kunshan Shengding SDC350KS contact angle meter with a liftable platform, use a 2 uL water droplet to perform a sessile drop test, and save the images of the contact between the water droplet and the glass slide at different times. Use the Laplace-Young equation to calculate the contact angle of the sample at the air-water interface.
[0150] UV spectrophotometer: Shimadzu UV-3600i Plus, Japan. The release rate test steps or test conditions of the core components in the microcapsules are as follows: 10 mL of cyclohexane is added to a certain mass of microcapsule freeze-dried powder. The core components were extracted from the mixture using an ultrasonic cell disruptor with a 1 / 8', 250 um micro-tip. Subsequently, the absorbance of the extract was recorded at 236 nm using a UV spectrophotometer to determine the mass of the lost core components and thus calculate the loss rate. The release rate was calculated using the formula: , , , Wherein, m0 is the total mass of added limonene; m1 is the theoretical mass of microcapsules before freeze-drying; m2 is the actual mass of microcapsules after freeze-drying; C1 is the measured limonene concentration; C2 is the loading rate before UV irradiation; C3 is the loading rate after UV irradiation. V1 is the volume of added cyclohexane, which is 10 mL in this test.
[0151] Example 1. Nanoparticles 1. Prepare a 2 wt% soy protein isolate aqueous solution, stir at 600 r for 2 h, and store at 4 °C for 12 h. Then place in a 90 °C water bath for 30 min and quickly cool to room temperature to obtain a soy protein isolate dispersion.
[0152] 2. Dissolve caffeic acid phenethyl ester in 10 mL of ethanol to prepare a 50 mM alcohol solution. Add anhydrous copper chloride with a final concentration of 0.2 mol% as a catalyst, then add 680 uL of hydrogen peroxide solution (final concentration 3 wt%) as an oxidant, and stir and oxidize at 25°C at a speed of 300 r for 10 min to obtain a hydroalcoholic solution of the quinone compound.
[0153] 3. The hydroalcoholic solution of the quinone compound was slowly adjusted to neutral with 0.5 M sodium hydroxide, then added to the soy protein isolate dispersion, and the mixed solution was adjusted to pH 8.5 with 1 M sodium hydroxide, and stirred at 35 ° C at a speed of 600 r for 3 h. After the reaction, the mixed solution was adjusted back to pH 7.0 with 0.5 M hydrochloric acid and the insoluble matter was separated, and the obtained clear solution was freeze-dried to obtain nanoparticles.
[0154] UV-visible absorption spectra Figure 1 As shown, the nanoparticles (b) have obvious peaks at 330 nm and 690 nm compared to the soy protein isolate (a), indicating that the nanoparticles have successfully reacted with caffeic acid phenethyl ester and have obvious ultraviolet and visible light absorption capabilities.
[0155] DLS test Figure 2 As shown in the figure, the average particle size of the single peak of the nanoparticles before illumination is 48 nm, and the PDI is 0.272; the average particle size of the single peak after illumination is 22 nm, and the PDI is 0.134. This indicates that the nanoparticles undergo cis-trans isomerization after illumination, resulting in a smaller particle size and more uniform distribution.
[0156] ABTS and FRAP tests Figure 3 As shown in Figures a and b, the antioxidant effect of 10 mg / mL nanoparticles is equivalent to 1.10 mM and 4.16 mM Trolox (antioxidant) equivalents, respectively, showing a strong total antioxidant capacity.
[0157] In addition, the DPPH radical scavenging rate of 10 mg / mL nanoparticles was 62.62%, indicating that they have free radical scavenging ability.
[0158] Example 2: Pickering emulsion containing 5 v / v% limonene The nanoparticles prepared in Example 1 were redissolved in deionized water to prepare a 10 mg / mL aqueous solution, 5 v / v% of limonene was added, and then emulsified at 8000 rpm for 3 min using a high-speed disperser and stored at 4°C for 12 h to obtain a Pickering emulsion containing 5 v / v% of limonene.
[0159] TEM test Figure 4 As shown, the complete emulsion structure can be observed.
[0160] SEM test Figure 5 Figure 2 shows the structure of the Pickering emulsion with nanoparticles adsorbed on the droplet surface.
[0161] DLS test results are as follows Figure 6As shown in the figure, the average droplet diameter of the emulsion before illumination was 411.6 nm and the PDI was 0.316. The average droplet diameter after illumination was 326.9 nm and the PDI was 0.251.
[0162] The above results indicate that the nanoparticles are photoresponsive at the emulsion interface, and the Pickering emulsion loaded with 5 v / v% limonene has a smaller particle size and a more uniform distribution after illumination.
[0163] Example 3. Preparation of Pickering emulsion containing 10 v / v% limonene The nanoparticles prepared in Example 1 were redissolved in deionized water to prepare a 5 mg / mL aqueous solution, 10 v / v% limonene was added, and then emulsified at 8000 rpm for 3 min using a high-speed disperser and stored at 4°C for 12 h to obtain a Pickering emulsion.
[0164] DLS test results are as follows Figure 7 As shown in the figure, the average droplet diameter of the emulsion before illumination was 386.7 nm and the PDI was 0.274. The average droplet diameter after illumination was 294.1 nm and the PDI was 0.192.
[0165] The above results indicate that the nanoparticles are photoresponsive at the emulsion interface, and the particle size of the Pickering emulsion loaded with 10 v / v% limonene becomes smaller and more evenly distributed after illumination.
[0166] Example 4: Preparation of Pickering emulsion containing 50 v / v% peppermint essential oil The nanoparticles were redissolved in deionized water to prepare a 1 mg / mL aqueous solution, 50 v / v% of peppermint essential oil was added and then emulsified using a high-speed disperser at 8000 rpm for 3 min and stored at 4°C for 12 h to obtain a Pickering emulsion.
[0167] DLS test results are as follows Figure 8 As shown in the figure, the average droplet diameter of the emulsion before illumination was 1415 nm and the PDI was 0.310. The average droplet diameter after illumination was 767.2 nm and the PDI was 0.116.
[0168] The results show that the nanoparticles are photoresponsive at the emulsion interface, and the Pickering emulsion loaded with 50 v / v% peppermint essential oil has a small particle size and uniform distribution after illumination.
[0169] The test results of DLS zeta potential are as follows: Fig. 9 As shown in the figure, the zeta potential of the emulsion showed a multi-peak distribution before illumination, and a single-peak distribution after illumination, indicating that illumination changed the adsorption behavior of nanoparticles at the emulsion interface, reorganized the emulsion interface structure, and made the zeta potential distribution more uniform.
[0170] Example 5. Preparation of Pickering Emulsion with 74 v / v% Peppermint Essential Oil The nanoparticles were redissolved in deionized water to prepare a 2 mg / mL aqueous solution, 74 v / v% of peppermint essential oil was added and then emulsified at 10000 rpm for 3 min using a high-speed disperser and stored at 4°C for 12 h to obtain a high internal phase Pickering emulsion.
[0171] Emulsion appearance picture Fig.10 As shown, it can be found that the emulsion after illumination underwent obvious oil phase precipitation and color lightening, indicating that the stability of the high internal phase emulsion is easily affected by the light responsiveness of the nanoparticles, and the oil phase is released by the reorganization of the emulsion interface structure.
[0172] Example 6: Preparation of a grafted product containing caffeic acid phenethyl ester as raw material Prepare 25 mL of 30 mM caffeic acid phenethyl ester in tert-butyl alcohol. Take 0.5 mol% anhydrous copper chloride as a catalyst, then quickly add 1.2 mL of hydrogen peroxide solution (3 wt%) as an oxidant, stir and oxidize at 300 r for 15 min at 25°C to obtain a hydroalcoholic solution of quinone compounds. Then add carboxymethyl chitosan powder to it to prepare a 0.05 wt% solution, rotate at 600 r until it is completely dispersed, and then add 30 mL of deionized water to form a co-solvent. Use 1M sodium hydroxide to adjust the pH of the co-solvent to 8.0, and stir at 800 r at 40°C for 6 h. After the reaction, adjust the pH to 7.0 with 0.1 M acetic acid, separate the insoluble matter, and freeze-dry the resulting clear liquid to obtain the grafted product.
[0173] The Fourier transform infrared spectra of the grafted product and carboxymethyl chitosan are as follows: Fig.11 As shown, the grafted product is at 1740 cm -1 There is an obvious absorption peak at 3420 cm, which is the C=O stretching vibration peak. Compared with carboxymethyl chitosan, the grafted product obtained by reacting with caffeic acid phenethyl ester has a peak at 3420 cm -1 、1461 cm -1 and 1052 cm -1 The characteristic peaks of 2923 cm-1 were weakened and disappeared to varying degrees, belonging to the stretching vibration of -NH2, the bending vibration of NH and the stretching vibration of COC, respectively, which indicated that the amino groups of caffeic acid phenethyl ester and carboxymethyl chitosan were cross-linked. -1 and 2853 cm -1 The peak intensities of -CH2 and -CH at 37° increased significantly, further proving the formation of grafted products.
[0174] ABTS and FRAP tests Fig.12 As shown in Figures ab, the antioxidant effect of 0.15 wt% grafted polymer is equivalent to 1.20 mM and 4.06 mM Trolox equivalents, respectively, showing strong total antioxidant capacity.
[0175] In addition, the DPPH radical scavenging rate of 0.15 wt% grafted material was 67.17%, indicating that it has the ability to scavenge free radicals.
[0176] Example 7: Preparation of a grafted product containing caffeic acid benzyl ester as raw material Prepare 25 mL of 50 mM caffeic acid benzyl ester in tert-butyl alcohol. Take 1 mol% anhydrous copper chloride as a catalyst, then quickly add 0.8 mL of hydrogen peroxide solution (3 wt%) as an oxidant, stir and oxidize at 300 r for 15 min at 25 ℃ to obtain a hydroalcoholic solution of quinone compounds. Then add carboxymethyl chitosan powder to it to prepare a 0.2wt% solution, rotate at 600 r until it is completely dispersed, and then add 30 mL of deionized water to form a co-solvent. Use 1 M sodium hydroxide to adjust the pH of the co-solvent to 8.0, and stir at 800 r at 40 ℃ for 6 h. After the reaction, adjust the pH to 7.0 with 0.1 M acetic acid, separate the insoluble matter, and freeze-dry the resulting clear liquid to obtain the grafted product.
[0177] The grafted material was redissolved in a co-solvent to prepare a 0.05 wt% solution, 10 v / v% peppermint essential oil was added, deionized water was used as the dialysate, the molecular weight cutoff of the dialysis bag was 3500 Da, the dialysis time was 6 h, and the water was changed every 3 h to obtain microcapsules.
[0178] Laser confocal microscopy of microcapsules Fig.13 As shown, (a) is the superposition of the core-shell structure, (b) is the core component stained with Nile red, and (c) is the shell structure stained with calcium fluoride white, which proves that the core component is successfully encapsulated in the shell structure to form a microcapsule. The air-water interface contact angle of the graft is ≥60°, and the average particle size of the microcapsule is 500 nm-1.5um.
[0179] Example 8: Preparation of a grafted product containing caffeic acid n-octyl ester as raw material Prepare 25 mL of 10 mM caffeic acid n-octyl ester in tert-butyl alcohol. Take 0.2 mol% anhydrous copper chloride as a catalyst, then quickly add 1 mL of hydrogen peroxide solution (3 wt%) as an oxidant, stir and oxidize at 300 r for 15 min at 25°C to obtain a hydroalcoholic solution of quinone compounds. Then add carboxymethyl chitosan powder to it to prepare a 0.4 wt% solution, rotate at 600 r until it is completely dispersed, and then add 30 mL of deionized water to form a co-solvent. Use 1 M sodium hydroxide to adjust the pH of the co-solvent to 8.0, and stir at 800 r at 40°C for 6 h. After the reaction, adjust the pH to 7.0 with 0.1 M acetic acid, separate the insoluble matter, and freeze-dry the resulting clear liquid to obtain the grafted product.
[0180] The grafted product was redissolved in a co-solvent to prepare a 0.2 wt% solution, 5 v / v% limonene was added, deionized water was used as the dialysate, the molecular weight cutoff of the dialysis bag was 3500 Da, the dialysis time was 12 h, and the water was changed every 3 h to obtain microcapsules.
[0181] The air-water contact angle of the graft prepared using 10 mM caffeic acid n-octyl ester was compared with that of carboxymethyl chitosan. Fig.14 As shown, the contact angle of carboxymethyl chitosan is 41.655°, while that of the graft is 63.711°, indicating that the hydrophobicity of carboxymethyl chitosan containing cinnamate groups is enhanced and microcapsules are successfully formed.
[0182] DLS test Fig.15 As shown in the figure, the average particle size of the microcapsules before illumination was 816 nm, and the PDI was 0.403; the average particle size after illumination was 663 nm, and the PDI was 0.272. This shows that the microcapsules are photoresponsive, and the microcapsules loaded with 5 v / v% limonene have smaller particle sizes and more uniform distribution after illumination.
[0183] Example 9: Preparation of a grafted product containing caffeic acid 1,1-dimethylallyl ester as raw material Prepare 25 mL of 20 mM caffeic acid-1,1-dimethylallyl ester in tert-butyl alcohol. Take 0.2 mol% anhydrous copper chloride as a catalyst, then quickly add 1 mL of hydrogen peroxide solution (3 wt%) as an oxidant, stir and oxidize at 300 r for 15 min at 25 °C to obtain a hydroalcoholic solution of quinone compounds. Then add carboxymethyl chitosan powder to it to prepare a 0.4 wt% solution, stir at 600 r until it is completely dispersed, and then add 30 mL of deionized water to form a co-solvent. Use 1 M sodium hydroxide to adjust the pH of the co-solvent to 8.0, and stir at 800 r at 40 °C for 6 h. After the reaction, adjust the pH to 7.0 with 0.1 M acetic acid, separate the insoluble matter, and freeze-dry the resulting clear liquid to obtain the grafted product. The grafted material was redissolved in a co-solvent to prepare a 0.1 wt% solution, 5 v / v% limonene was added, deionized water was used as the dialysate, the molecular weight cutoff of the dialysis bag was 3500 Da, the dialysis time was 12 h, and the water was changed every 3 h to obtain microcapsules.
[0184] The air-water contact angle of the graft prepared using 20 mM caffeic acid-1,1-dimethylallyl ester was compared with that of carboxymethyl chitosan. Fig.16 As shown, the contact angle of carboxymethyl chitosan is 41.655°, while that of the graft is 73.337°, indicating that the hydrophobicity of carboxymethyl chitosan containing cinnamate groups is enhanced and microcapsules are successfully formed.
[0185] DLS test Fig.17 As shown in the figure, the average particle size of the microcapsules before illumination was 712 nm, and the PDI was 0.226; the average particle size after illumination was 459 nm, and the PDI was 0.169. This shows that the microcapsules are photoresponsive, and the microcapsules loaded with 5 v / v% limonene have smaller particle sizes and more uniform distribution after illumination.
[0186] The change of microcapsule release amount with illumination time is shown in the figure Fig.18 As shown in the figure, the release performance of the two types of microcapsules after illumination is significantly better than that of the control group. At 2 h of illumination, the two types of microcapsules showed a higher release efficiency, which was 10% and 15% higher than that of the control group, respectively. As the illumination time was extended to 4 h, this trend further expanded, and the release amount of the two types of microcapsules after illumination was 20% higher than that of the control group. After continuous illumination for 6 h, the release amount of limonene from the two microcapsules was stable at about 39%, showing good light responsiveness and light-controlled release ability. At this time, the release amount of the control group was 20%, which was lower than that of the microcapsules in the illumination group.
[0187] The results showed that the microcapsules promoted the release of core components under ultraviolet UV-340 irradiation.
[0188] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a light-responsive antioxidant preparation, characterized in that: The light-responsive antioxidant preparation is a Pickering emulsion, and the method comprises: A: Dispersing a biopolymer in water at a mass concentration of 1 to 10 wt%, fully mixing, incubating at 4±2°C, then at 90±10°C, and rapidly cooling to room temperature to obtain a biopolymer dispersion; the biopolymer is soy protein isolate; B: dissolving a cinnamate derivative in ethanol to form an alcohol solution with a cinnamate derivative concentration of 20 to 80 mM, using 0.05 to 2 mol% copper ions as a catalyst and 3±2 wt% hydrogen peroxide as an oxidant, mixing and oxidizing at 10 to 30° C. to obtain a hydroalcoholic solution of a quinone compound; the cinnamate derivative is caffeic acid phenethyl ester; C: adjusting the aqueous alcohol solution of the quinone compound to neutral, mixing it with the biopolymer dispersion, adjusting the pH of the mixed solution to 8.5±1, mixing thoroughly, and reacting for 2 to 8 hours; adjusting the reaction product to neutral, freeze-drying, and obtaining nanoparticles; D: Dissolve 0.5-20 mg / mL nanoparticles in water, add aromatic compounds, and emulsify to obtain the Pickering emulsion; the aromatic compounds include limonene or peppermint essential oil; the volume fraction of the aromatic compounds is 3-80 v / v%.
2. The method for preparing the light-responsive antioxidant preparation according to claim 1, characterized in that: In C, after the reaction product is adjusted to neutrality, the process further comprises: removing insoluble matter, harvesting the clear liquid and performing freeze-drying.
3. The method for preparing the light-responsive antioxidant preparation according to claim 1, characterized in that: In D, 1-15 mg / mL of nanoparticles were dissolved in water.
4. A method for preparing a light-responsive antioxidant preparation, characterized in that: The light-responsive antioxidant preparation is a microcapsule, and the method comprises: A': dissolving a cinnamate derivative in tert-butyl alcohol to form an alcohol solution with a cinnamate derivative concentration of 5 to 80 mM, using 0.05 to 2 mol% copper ions as a catalyst and hydrogen peroxide as an oxidant, mixing and oxidizing at 10 to 30°C to obtain a hydroalcoholic solution of a quinone compound; the cinnamate derivative is caffeic acid phenethyl ester, caffeic acid benzyl ester, caffeic acid n-octyl ester or caffeic acid-1,1-dimethylallyl ester; the molar ratio of the cinnamate derivative to hydrogen peroxide is 1:0.8 to 3; B': dispersing a biopolymer in a hydroalcoholic solution of the quinone compound, and then adding an equal volume of water to form a cosolvent; the biopolymer is carboxymethyl chitosan, and its mass concentration is 0.1-2wt%; C': adjust the pH of the mixed solution to 8.0±0.6, mix thoroughly at 30-45°C, and react for 2-8 hours; adjust the reaction product to neutral, freeze-dry, and obtain the grafted product; D': Dissolve 0.02-0.8 wt% of the grafted material in water, add aromatic compounds, and retain the portion with a molecular weight greater than 3500 Da by dialysis to obtain microcapsules with light-responsive properties; the aromatic compounds include limonene or peppermint essential oil; the volume fraction of the aromatic compounds is 1-20 v / v%.
5. The method for preparing the light-responsive antioxidant preparation according to claim 4, characterized in that: In D', the mass concentration of the grafted substance is 0.05-0.2 wt %.
6. The method for preparing the light-responsive antioxidant preparation according to claim 4, characterized in that: In D', the dialysis method uses water as the dialysate.
7. The method for preparing the light-responsive antioxidant preparation according to claim 1 or 4, characterized in that: The copper ions include copper ions derived from copper chloride or copper sulfate.
8. The method for preparing the light-responsive antioxidant preparation according to claim 1 or 4, characterized in that: The quinone type compound includes: a semiquinone compound, an o-benzoquinone compound or a free radical polymer.
9. A light-responsive antioxidant preparation, prepared by the method according to any one of claims 1 to 8.
10. Use of the light-responsive antioxidant preparation according to claim 9 for preparing cosmetics or skin care products, wherein the aromatic compound can be released in a controlled manner.
Citation Information
Patent Citations
Tea tree oil antibacterial microcapsule and preparation method and application thereof
CN103070811A
Nano cellulose containing cinnamyl functional group and preparation method and application of nano cellulose
CN107254002A
Preparation method and application of polymer hollow microcapsule
CN107868161A
Preparation method of photoresponsive cinnamic acid derivative-grafted nanocellulose
CN109608556A
Photo-thermal dual-responsiveness chitosan derivative as well as preparation method and application thereof
CN111533848A